Edukasi dan Implementasi Lubang Resapan Biopori untuk Mitigasi Banjir dan Pengelolaan Sampah Organik - Akhmad, Andi Saputra; Ikhtisholiyah, Ikhtisholiyah; Suprihatin, Hasti; Sa’idah, Nazilatus; Mantovani, Muhammad Dias Echa (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Iker-iker Geger Village is a village located in Cerme District, Gresik Regency. that often experiences seasonal flooding due to rainwater runoff that cannot be absorbed optimally by the soil, especially during high rainfall in the rainy season. The flat topography, clay soil type, and suboptimal drainage system exacerbate this condition. In addition, household organic waste management in the village is still limited, with most waste being burnt or dumped into waterways, contributing to drainage blockages and environmental pollution. These problems require a simple yet impactful approach, one of which is through the application of biopore infiltration pit technology that has proven effective in increasing groundwater absorption, reducing the volume of surface runoff, as well as processing organic waste into compost that is beneficial for local agriculture. This community service program aims to provide education and direct assistance to the people of Iker-Iker Geger Village in making and utilizing biopores as a sustainable environmental solution. This activity involves elements of the community, village officials, and students, with a participatory approach that is expected to increase environmental awareness and encourage village independence in overcoming the problems of inundation and organic waste. Through this program, the community not only gained technical skills but also instilled a spirit of mutual cooperation in protecting the environment, in line with the principles of sustainable development and local wisdom.